Experience in the Management of Vaginal Cuff Dehiscence and Evisceration: A Retrospective 37-Year Single-Center Study - Ma, Xiao; Cao, Dong-Yan; Dai, Yu-Xin (Frontiers in Surgery, 2022)
Purpose: Vaginal cuff dehiscence (and evisceration) (VCD(E)) is an extremely rare and late-onset complication of total hysterectomy (TH). Limited evidence is available to guide clinicians in managing VCD(E). This study aimed to summarize the clinical characteristics of patients with VCD(E) treated in our center and share our experience in managing VCD(E). Patients and methods: From 1983 to 2020, a total of 14 cases of VCD(E), including 10 cases in our hospital and 4 cases in other hospitals, were included. Medical records were reviewed to summarize the clinical features and management of VCD(E). Results: The incidence of VCD(E) in our hospital was 10/46993 (0.02%), and all 10 patients underwent laparoscopic hysterectomy. The median TH-to-VCD(E) interval was 3.13 months (8 days–27.43 months), and 11/14 (78.57%) patients experienced VCD(E) after coitus. The 3 major symptoms included abdominal pain in 11 patients, irregular vaginal bleeding in 8, and sensation of bulging or prolapsed organs in 4. Except for 2, most patients presented to our hospital within 72 hours since the onset of the discomfort. All 14 cases were diagnosed through speculum examination: 3 had simple VCD, and 11 had VCDE. The protruding bowels of 4 patients were immediately manually repositioned in the emergency department without anesthesia. Regarding the surgical approach, 11 patients underwent simple transvaginal, 2 patients underwent laparoscopic-vaginal combined (transvaginal cuff closures), and 1 patient underwent laparoscopic. All but 1 patient did not undergo resection of the eviscerated organs. The median follow-up period was 39.33 (7.9–159.33) months. No patients showed any evidence of recurrence to date. Conclusions: Laparoscopic hysterectomy is a risk factor for VCD(E), and early initiation of sexual intercourse is the most common trigger of VCD(E). Clinicians should educate patients to postpone sexual intercourse for at least 3–6 months after TH. Immediate medical attention and patient-specific surgical management are crucial to avoid serious complications.